Measurement of the time-dependent CP-violating asymmetry in B-0 -> K-S(0)pi(0)gamma decays - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; Pappagallo, M; et al. (2005)
We present a measurement of the time-dependent CP-violating asymmetry in B0→K*0γ decays with K*0→KS0π0 based on 232×106 Υ(4S)→BB̄ decays collected with the BABAR detector at the PEP-II asymmetric-energy e+e- collider at SLAC. In a sample containing 157±16 signal decays, we measure SK*0γ=-0.21±0. 40±0.05 and CK*0γ=-0.40±0.23±0.03, where the first error is statistical and the second systematic. We also explore B0→KS0π0γ decays with 1.1